Case Report: Two New Cases of Autosomal-Recessive Hypertrophic Cardiomyopathy Associated With TRIM63-Compound Heterozygous Variant - Andreeva, Sofiya; Chumakova, Olga; Karelkina, Elena; Lebedeva, Viktoriya; Lubimtseva, Tamara; Semenov, Andrey; Nikitin, Alexey; Speshilov, Gleb; Kozyreva, Alexandra; Sokolnikova, Polina; Zhuk, Sergey; Fomicheva, Yuliya; et al. (Frontiers in Genetics, 2022)
Hypertrophic cardiomyopathy (HCM) is one of the most common hereditary diseases, and it is associated with fatal complications. The clinical heterogeneity of HCM requires risk prediction models to identify patients at a high risk of adverse events. Most HCM cases are caused by mutations in genes encoding sarcomere proteins. However, there are HCM associated with rare genetic variants with limited data about its clinical course and prognosis, and existing risk prediction models are not validated for such patients` cohorts. TRIM63 is one of the rare genes recently described as a cause of HCM with autosomal-recessive inheritance. Here we present two cases of HCM associated with TRIM63-compound heterozygous variants in young male sportsmen. They demonstrated progressively marked hypertrophy, advanced diastolic dysfunction, a significant degree of fibrosis detected by magnetic resonance imaging, and clear indications for implantable cardioverter-defibrillator. One of the cases includes the first description of TRIM63-HCM with extreme hypertrophy. The presented cases are discussed in the light of molecular consequences that might underlie cardiac and muscle phenotype in patients with mutations of TRIM63, the master regulator of striated muscle mass.